Preparation method of hollow mesoporous carbon spheres with adjustable pore structures
By dispersing the silica emulsified microspheres in the ammonia ethanol system and using CTAC as a surfactant, hollow mesoporous carbon spheres with adjustable pore structure and pore size are constructed, solving the problem of difficult control of pore structure and pore size in the prior art, and achieving efficient and low-cost mesoporous carbon sphere preparation.
Patent Information
- Application Number
- CN202411789302.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to accurately control the pore structure and pore size of mesoporous carbon spheres, and the production cost is high and the yield is low, which limits the application of mesoporous carbon spheres in the fields of adsorption and catalysis.
By dispersing in an ammonia ethanol system to produce silica emulsified microspheres, and using CTAC as a surfactant, hollow mesoporous carbon spheres with adjustable pore structure and pore size were constructed through the alcoholization reaction and carbonization process.
It realizes precise control of mesoporous carbon sphere channel structure and pore size, improves specific surface area and pore structure integrity, reduces preparation costs, increases yield, and is suitable for a variety of application fields.
Smart Images

Figure CN119706809A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a method for preparing hollow mesoporous carbon spheres with adjustable pore structures. Background Art
[0002] In recent years, mesoporous materials such as mesoporous silicon and mesoporous carbon have shown potential for broad application prospects in adsorption, catalysis, drug delivery, energy storage and conversion, etc. Mesoporous carbon spheres not only have the properties of mesoporous materials and carbon's excellent properties such as good electrical conductivity, thermal / mechanical stability, and chemical inertness, but also have attracted widespread attention in the fields of energy storage and conversion, biomedicine, etc. due to their regular spherical appearance.
[0003] After carbonization (graphitization), ordinary solid carbon spheres have a certain degree of adsorption capacity, but there are still problems such as high filling degree, large conductive loss, and low dielectric constant. Therefore, in order to further improve the physical and chemical adsorption effect and the photoelectric physics electromagnetic wave absorption effect, it is necessary to design the microstructure of carbon spheres; and among them, designing holes (mesopores) on the surface of carbon spheres and making hollow cavity structures inside is a very good solution, which can lighten the carbon spheres, reduce their filling degree, increase the specific surface area and the degree of three-dimensional structure, which is conducive to the next step of application.
[0004] At present, the known preparation methods of porous carbon spheres, such as hard template method, soft template method or self-template method, are to polymerize and crosslink the fluid precursor (such as phenolic resin, monosaccharide and disaccharide dispersed carbohydrates, etc.) and the template agent in different reaction systems and at different temperatures, and then carbonize. However, these methods have many limitations, including: (1) the selection of the template agent is not very detailed and difficult to choose, or the reaction temperature is high and difficult to operate and control; (2) the pore structure of the surface mesoporous shell layer and the pore size of the surface mesopores cannot be accurately controlled and designed (the adjustment range is too large); (3) there is no potential for expanding production, the preparation cost is high, and the output is low, which is a severe challenge to the development and promotion of mesoporous carbon spheres. The introduction of the hollow cavity is based on the Stober method, using the in-situ generated silica emulsified particles as the template for both the hollow and the surface mesopores, solving two problems in one step, but there are also problems in the selection of raw materials and reaction systems for the design and regulation of the internal cavity and the surface mesopores. At present, there is no rigorous and standardized technical method.
[0005] Based on this, the present invention constructs a method for preparing hollow mesoporous carbon spheres with adjustable pore structure. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing hollow mesoporous carbon spheres with adjustable pore structure, comprising the following steps:
[0007] Step S1, mixing ethanol, water and aqueous ammonia to prepare an aqueous ammonia ethanol solution;
[0008] Step S2, adding tetraethyl orthosilicate to an ammonia ethanol solution to carry out an alcoholization reaction, and then adding a mixed solution of water and ethanol to continue the reaction;
[0009] Step S3, adding a template solution to the reaction solution of step S2 for reaction, wherein the template solution is a 20-35wt.% CTAC solution, and the amount of the template solution is 1 / 10 of the volume of the reaction solution of step S2;
[0010] Step S4, adding resorcinol, formaldehyde solution and tetraethyl orthosilicate to the reaction solution of step S3 to carry out reaction;
[0011] Step S5, transferring the reaction solution of step S4 to a hydrothermal reactor for reaction;
[0012] Step S6, washing the reactant obtained in step S5 by centrifugation with ethanol and drying in vacuum;
[0013] Step S7, carbonizing the dried product in step S6 under a nitrogen atmosphere;
[0014] Step S8, adding the carbonized product of step S7 to an ammonium bifluoride solution for reaction, removing silicon, washing with water and then drying to obtain hollow mesoporous carbon spheres.
[0015] Furthermore, in step S1, the volume ratio of ethanol, water and ammonia water in the ammonia ethanol solution is 100:20:3.
[0016] Furthermore, in step S2, the amount of ammonia ethanol solution is 60-80 ml, the volume ratio of tetraethyl orthosilicate to ammonia water in the ammonia ethanol solution is 5:3, and the reaction conditions are 20-45°C, 300-500rpm for 5-12h; the amount of the mixed solution of water and ethanol is 300-400 ml, the volume ratio of water and ethanol is 6:1, and the conditions for continuing the reaction are 20-45°C, 300-500rpm for 15-40min.
[0017] Furthermore, in step S3, the reaction conditions are 20-45° C., 300-500 rpm, and 15-40 min.
[0018] Furthermore, in step S4, the amount of resorcinol used is 0.5-1.5 g, the amount of formaldehyde solution used is 0.75-2 ml, the amount of tetraethyl orthosilicate used is 3-5 ml, and the reaction conditions are 20-45° C., 300-500 rpm, and the reaction time is 14-20 h.
[0019] Furthermore, in step S5, the reaction conditions are 100-150° C. for 20-30 hours.
[0020] Furthermore, in step S6, the centrifugal washing with ethanol is performed by centrifugal washing with ethanol at a rotation speed of 9000-11000 rpm, and the vacuum drying conditions are 50-70° C. and 12 h.
[0021] Furthermore, in step S7, the carbonization conditions are to increase the temperature to 700-900° C. at a heating rate of 3-8° C. / min and keep the temperature for 2-5 hours.
[0022] Furthermore, in step S8, the concentration of the ammonium bifluoride solution is 10-30 wt.%, the reaction conditions are 20-60° C., 300-600 rpm, 12 h, and the drying conditions are 50-75° C.
[0023] The present invention uses surfactants (such as F-127, CTAB, and CTAC) of different concentration ratios to aggregate on emulsified microspheres generated by the first hydrolysis of tetraethyl orthosilicate. Since these surfactants have a carbon long skeleton morphology, they have aggregation states such as "branch divergence" with one end adhered and the other diverging, and covalent bond dense adsorption. Then, the microspheres generated by the second hydrolysis of tetraethyl orthosilicate are bound / adsorbed and attached to the original silicon dioxide microspheres that have gradually grown into larger ones. Then, the reaction, carbonization, and silicon removal are continued to obtain hollow mesoporous carbon spheres (HMCNs) with different pore structures and pore sizes. In particular, the inventors found that compared with other active agents, the ability of CTAC to attach and re-adsorb can be precisely controlled by concentration, temperature and hydrolysis state, and the scale-up of production does not affect the morphology and pore structure. In addition, the HMCNs prepared by this method have smaller surface mesopore diameters as the specific surface area increases, which also confirms the design of CTAC for the surface pore structure: the "branch-like structure" radiating from the ends provides more sites, but the silica microspheres bound on the "branches" are constrained by the size of the main skeleton and cannot be too large. Therefore, the surface mesopores formed after silicon removal in the subsequent step cannot be too large, which is manifested as the larger the specific surface area, the smaller the pore diameter and pore volume obtained by the test.
[0024] The present invention selects to disperse and generate silica emulsified microspheres in an ammonia ethanol system, then introduces a carbon source (resorcinol and formaldehyde) at room temperature, and uses CTAC as a surfactant as a tool for designing the mesoporous channels of carbon spheres, thereby constructing a method for preparing hollow mesoporous carbon spheres with adjustable surface channel structures. The preparation method of the present invention can more accurately design the surface mesoporous layer and the mesoporous pore size.
[0025] The method of the present invention can be used to prepare nanostructured ... 2 / g, and the pore size gradually increased to about 20nm, while the surface area decreased to 300m 2 / g, and the shell thickness is between 70-80nm and 20-30nm.
[0026] The present invention prepares hollow mesoporous carbon spheres based on the soft template method, and controls the surface mesoporous layer and mesopore size of the mesoporous carbon spheres through the template aqueous solution, so that the hollow mesoporous carbon spheres have different and adjustable pore structures and skeletons, making them more suitable for precise and stable loads and other application fields. The stable preparation method of hollow mesoporous carbon spheres of the present invention provides versatility for the preparation of other carbon spheres. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 TEM and SEM images of the hollow mesoporous carbon sphere sample A in Example 1.
[0028] Figure 2 TEM and SEM images of the hollow mesoporous carbon sphere B sample in Example 2.
[0029] Figure 3 TEM and SEM images of the hollow mesoporous carbon sphere C sample in Example 3.
[0030] Figure 4 TEM and SEM images of the hollow mesoporous carbon sphere D sample in Example 4.
[0031] Figure 5 TEM and SEM images of the hollow mesoporous carbon sphere E sample in Example 5.
[0032] Figure 6 TEM and SEM images of the hollow mesoporous carbon sphere F sample in Example 6. DETAILED DESCRIPTION
[0033] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.
[0034] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0035] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0036] In the following examples, the concentration of aqueous ammonia is 25%-28%, the purity of tetraethyl orthosilicate (TEOS) is 98%, and the concentration of formaldehyde solution is 37%.
[0037] Example 1
[0038] Step S1, preparing 80 ml of an ammonia-ethanol solution in a volume ratio of ethanol: purified water: ammonia water = 100:20:3, and mixing at 25° C. and a stirring rate of 500 rpm for 15 minutes;
[0039] Step S2, adding silicon source TEOS to the mixed solution according to the volume ratio of tetraethyl orthosilicate: ammonia water = 5:3, and reacting at 25°C and 500rpm for 9h; then preparing a mixed solution of water and ethanol in a volume ratio of water: ethanol = 6:1 with a total volume of 350ml, adding it to the reaction solution, and continuing the reaction under the same conditions for 20min;
[0040] Step S3, preparing a 5 wt % F-127 aqueous solution according to 1 / 10 of the volume of the reaction solution, and rapidly adding it dropwise into the reaction solution, reacting at 25° C. and 500 rpm for 20 min;
[0041] Step S4, adding 1 g of resorcinol and 1.5 ml of formaldehyde solution to the reaction solution, and then adding 4 ml of TEOS dropwise to the reaction solution, and reacting at 25° C. and 500 rpm for 18 h;
[0042] Step S5, transferring the reaction solution to a polytetrafluoroethylene reactor with a filling degree of 80%, reacting at 130° C. for 24 hours, and then cooling naturally;
[0043] Step S6, collecting the hydrothermal reaction product by centrifugation, washing with ethanol at a speed of 11000 rpm, repeating 3-5 times, collecting the obtained rose-red product, placing it in a vacuum oven set at a temperature of 50° C., and vacuum drying overnight;
[0044] Step S7, spread the dried product in a crucible and put it into a tube furnace, set the heating rate to 5°C / min, introduce flowing nitrogen, heat to 850°C, keep the temperature for 4 hours for carbonization, and then cool naturally;
[0045] Step S8, putting the carbonized black product into a 20wt% ammonium bifluoride aqueous solution prepared in advance, stirring in a water bath at 50°C and 750rpm overnight, then vacuum filtering and washing with pure water, and finally drying by air at 65°C to obtain a hollow mesoporous carbon sphere A sample.
[0046] Figure 1 The scanning electron microscope and transmission electron microscope test results show that the shape is irregular and mostly aggregated, without hollow cavities. Therefore, it can be known that F-127 as a surfactant cannot be used to prepare hollow mesoporous carbon spheres with adjustable pore structure.
[0047] Example 2
[0048] Step S1, preparing 80 ml of an ammonia-ethanol solution in a volume ratio of ethanol: purified water: ammonia water = 100:20:3, and mixing at 25° C. and a stirring rate of 500 rpm for 15 minutes;
[0049] Step S2, adding silicon source TEOS to the mixed solution according to the volume ratio of tetraethyl orthosilicate: ammonia water = 5:3, and reacting at 25°C and 500rpm for 9h; then preparing a mixed solution of water and ethanol in a volume ratio of water: ethanol = 6:1 with a total volume of 350ml, adding it to the reaction solution, and continuing the reaction under the same conditions for 20min;
[0050] Step S3, preparing a 25 wt % CTAB aqueous solution according to 1 / 10 of the volume of the reaction solution, and rapidly adding it dropwise into the reaction solution, and continuing the reaction at 25° C. and 500 rpm for 20 min;
[0051] Step S4, adding 1 g of resorcinol and 1.5 ml of formaldehyde solution to the reaction solution, and then adding 4 ml of TEOS dropwise to the reaction solution, and continuing to stir and react at 25° C. and 500 rpm for 18 hours;
[0052] Step S5, transferring the reaction solution to a polytetrafluoroethylene reactor with a filling degree of 80%, reacting at 130° C. for 24 hours, and then cooling naturally;
[0053] Step S6, collecting the hydrothermal reaction product by centrifugation, washing with ethanol at a speed of 11000 rpm, repeating 3-5 times, collecting the obtained rose-red product, placing it in a vacuum oven set at a temperature of 50° C., and vacuum drying overnight;
[0054] Step S7, spread the dried product in a crucible and put it into a tube furnace, set the heating rate to 5°C / min, introduce flowing nitrogen, heat to 850°C, keep the temperature for 4 hours for carbonization, and then cool naturally;
[0055] Step S8, putting the carbonized black product into a 20wt% ammonium bifluoride aqueous solution prepared in advance, stirring in a water bath at 50°C and 750rpm overnight, then vacuum filtering and cleaning with pure water, and finally drying by air at 65°C to obtain a hollow mesoporous carbon sphere B sample.
[0056] Figure 2 This is a characterization picture of the scanning electron microscope and transmission electron microscope tests. It can be seen that a cavity has been formed, but the walls are thin and adhere to each other, and the shape is like chicken intestines. It is not spherical and has no surface pore structure. It can be seen that CTAB as a surfactant cannot be used to prepare hollow mesoporous carbon spheres with adjustable pore structure.
[0057] Example 3
[0058] Step S1, preparing 80 ml of an ammonia-ethanol solution in a volume ratio of ethanol: purified water: ammonia water = 100:20:3, and mixing at 25° C. and a stirring rate of 500 rpm for 15 minutes;
[0059] Step S2, adding silicon source TEOS to the mixed solution according to the volume ratio of tetraethyl orthosilicate: ammonia water = 5:3, and reacting at 25°C and 500rpm for 9h; then preparing a mixed solution of water and ethanol in a volume ratio of water: ethanol = 6:1 with a total volume of 350ml, adding it to the reaction solution, and continuing the reaction under the same conditions for 20min;
[0060] Step S3, preparing a 20 wt % CTAC aqueous solution according to 1 / 10 of the volume of the reaction solution, and rapidly adding it dropwise into the reaction solution, and reacting at 25° C. and 500 rpm for 20 min;
[0061] Step S4, adding 1 g of resorcinol and 1.5 ml of formaldehyde solution to the reaction solution, and then adding 4 ml of TEOS dropwise to the reaction solution, and continuing to stir and react at 25° C. and 500 rpm for 18 hours;
[0062] Step S5, transferring the reaction solution to a polytetrafluoroethylene reactor with a filling degree of 80%, reacting at 130° C. for 24 hours, and then cooling naturally;
[0063] Step S6, collecting the hydrothermal reaction product by centrifugation, washing with ethanol at a speed of 11000 rpm, repeating 3-5 times, collecting the obtained rose-red product, placing it in a vacuum oven set at a temperature of 50° C., and vacuum drying overnight;
[0064] Step S7, spread the dried product in a crucible and put it into a tube furnace, set the heating rate to 5°C / min, introduce flowing nitrogen, heat to 850°C, keep the temperature for 4 hours for carbonization, and then cool naturally;
[0065] Step S8, putting the carbonized black product into a 20wt% ammonium bifluoride aqueous solution prepared in advance, stirring in a water bath at 50°C and 750rpm overnight, then vacuum filtering and washing with pure water, and finally drying by air at 65°C to obtain a hollow mesoporous carbon sphere C sample.
[0066] Figure 3 The scanning electron microscope and transmission electron microscope test results show that it has formed a sphere with a hollow cavity, but the surface shell is about 25-35nm, which is relatively thin and can be observed to be more broken and the cavity is directly exposed and open. It is possible that the concentration of the CTAC aqueous solution is not enough to evenly disperse in the outer shell of the sphere and form a complete mesoporous channel structure. The BET surface area test of this sample shows that this sample is affected by the broken cavity and the specific surface area is only 238m 2 / g, but the pore size is greater than 16nm. It can be seen that although 20% CTAC aqueous solution can be used as a surfactant to make hollow mesoporous carbon spheres, they are mostly broken and have incomplete pore structures, making them unsuitable for subsequent practical applications such as loading.
[0067] Example 4
[0068] Step S1, preparing 80 ml of an ammonia-ethanol solution in a volume ratio of ethanol: purified water: ammonia water = 100:20:3, and mixing at 25° C. and a stirring rate of 500 rpm for 15 minutes;
[0069] Step S2, adding silicon source TEOS to the mixed solution according to the volume ratio of tetraethyl orthosilicate: ammonia water = 5:3, and reacting at 25°C and 500rpm for 9h; then preparing a mixed solution of water and ethanol in a volume ratio of water: ethanol = 6:1 with a total volume of 350ml, adding it to the reaction solution, and continuing the reaction under the same conditions for 20min;
[0070] Step S3, preparing a 25 wt % CTAC aqueous solution according to 1 / 10 of the volume of the reaction solution, and rapidly adding it dropwise into the reaction solution, and reacting at 25° C. and 500 rpm for 20 min;
[0071] Step S4, adding 1 g of resorcinol and 1.5 ml of formaldehyde solution to the reaction solution, and then adding 4 ml of TEOS dropwise to the reaction solution, and continuing to stir and react at 25° C. and 500 rpm for 18 hours;
[0072] Step S5, transferring the reaction solution to a polytetrafluoroethylene reactor with a filling degree of 80%, reacting at 130° C. for 24 hours, and then cooling naturally;
[0073] Step S6, collecting the hydrothermal reaction product by centrifugation, washing with ethanol at a speed of 11000 rpm, repeating 3-5 times, collecting the obtained rose-red product, placing it in a vacuum oven set at a temperature of 50° C., and vacuum drying overnight;
[0074] Step S7, spread the dried product in a crucible and put it into a tube furnace, set the heating rate to 5°C / min, introduce flowing nitrogen, heat to 850°C, keep the temperature for 4 hours for carbonization, and then cool naturally;
[0075] Step S8, the carbonized black product is put into a 20wt% ammonium bifluoride aqueous solution prepared in advance, stirred in a water bath at 50°C and 750rpm overnight, then vacuum filtered and cleaned with pure water, and finally dried at 65°C by air blast to obtain a hollow mesoporous carbon sphere D sample.
[0076] Figure 4The characterization diagram of the SEM and TEM test shows that the relatively perfect hollow mesoporous carbon spheres are seen. The long skeleton CTAC is evenly attached to the outer shell of the sphere like a "branch". The shell thickness (with divergent ends) is between 45-50nm. The spheres are intact and less broken. The BET surface area test of the sample shows that the average specific surface area is greater than 900m 2 / g, pore diameter of 4nm, pore volume of 0.96cm 3 / g, which is consistent with the inventor's expectation. The ability of the CTAC long skeleton with divergent ends to bind the silica microspheres is limited, and the pore size left after carbonization and silicon removal is relatively small. It can be seen that the 25wt% CTAC aqueous solution can prepare relatively perfect hollow mesoporous carbon spheres that meet the expected pore structure design for this reaction system.
[0077] Example 5
[0078] Step S1, preparing 80 ml of an ammonia-ethanol solution in a volume ratio of ethanol: purified water: ammonia water = 100:20:3, and mixing at 25° C. and a stirring rate of 500 rpm for 15 minutes;
[0079] Step S2, adding silicon source TEOS to the mixed solution according to the volume ratio of tetraethyl orthosilicate: ammonia water = 5:3, and reacting at 25°C and 500rpm for 9h; then preparing a mixed solution of water and ethanol in a volume ratio of water: ethanol = 6:1 with a total volume of 350ml, adding it to the reaction solution, and continuing the reaction under the same conditions for 20min;
[0080] Step S3, preparing a 30 wt % CTAC aqueous solution according to 1 / 10 of the volume of the reaction solution, and rapidly adding it dropwise into the reaction solution, and reacting at 25° C. and 500 rpm for 20 min;
[0081] Step S4, adding 1 g of resorcinol and 1.5 ml of formaldehyde solution to the reaction solution, and then adding 4 ml of TEOS dropwise to the reaction solution, and continuing to stir and react at 25° C. and 500 rpm for 18 hours;
[0082] Step S5, transferring the reaction solution to a polytetrafluoroethylene reactor with a filling degree of 80%, reacting at 130° C. for 24 hours, and then cooling naturally;
[0083] Step S6, collecting the hydrothermal reaction product by centrifugation, washing with ethanol at a speed of 11000 rpm, repeating 3-5 times, collecting the obtained rose-red product, placing it in a vacuum oven set at a temperature of 50° C., and vacuum drying overnight;
[0084] Step S7, spread the dried product in a crucible and put it into a tube furnace, set the heating rate to 5°C / min, introduce flowing nitrogen, heat to 850°C, keep the temperature for 4 hours for carbonization, and then cool naturally;
[0085] Step S8, the carbonized black product is put into a 20wt% aqueous solution of ammonium bifluoride prepared in advance, stirred in a water bath at 50°C and 750rpm overnight, then vacuum filtered and cleaned with pure water, and finally dried at 65°C by air to obtain a hollow mesoporous carbon sphere E sample.
[0086] Figure 5 The characterization diagram of the SEM and TEM test shows that another pore structure with dense surface adsorption is obtained. At this time, the CTAC skeleton is completely adsorbed on the outer shell of the sphere. The outer shell is thicker (dark in color) and the thickness is 40-55nm. A relatively perfect hollow mesoporous carbon sphere is obtained, and the shell thickness is between 40-75nm. The BET test of the sample shows that the specific surface area is 650m 2 / g, pore diameter of 6nm, pore volume of 1cm 3 / g, which is consistent with the inventor's expectation. When the CTAC skeleton is completely adsorbed on the outside of the sphere, the ability to bind the silica microspheres is improved and allows them to continue to hydrolyze and grow in an ammonia-ethanol environment. After carbonization and silicon removal, a larger and deeper pore structure than the "dendritic" divergent sphere shell can be obtained.
[0087] Example 6
[0088] Step S1, preparing 160 ml of an ammonia-ethanol solution according to a volume ratio of ethanol: purified water: ammonia water = 100:20:3, and mixing at 25° C. and a stirring rate of 500 rpm for 15 minutes;
[0089] Step S2, adding silicon source TEOS to the mixed solution according to the volume ratio of tetraethyl orthosilicate: ammonia water = 5:3, and reacting at 25°C and 500rpm for 9h; then preparing a mixed solution of water and ethanol in a volume ratio of water: ethanol = 6:1 with a total amount of 700ml, adding it to the reaction solution, and continuing to react under the same conditions for 20min;
[0090] Step S3, preparing a 30 wt % CTAC aqueous solution according to 1 / 10 of the volume of the reaction solution, and rapidly adding it dropwise into the reaction solution, and reacting at 25° C. and 500 rpm for 20 min;
[0091] Step S4, adding 2 g of resorcinol and 3 ml of formaldehyde solution to the reaction solution, and then adding 8 ml of TEOS dropwise to the reaction solution, and continuing to stir and react at 25° C. and 500 rpm for 18 h;
[0092] Step S5, transferring the reaction solution to a polytetrafluoroethylene reactor with a filling degree of 80%, reacting at 130° C. for 24 hours, and then cooling naturally;
[0093] Step S6, collecting the hydrothermal reaction product by centrifugation, washing with ethanol at a speed of 11000 rpm, repeating 3-5 times, collecting the obtained rose-red product, placing it in a vacuum oven set at a temperature of 50° C., and vacuum drying overnight;
[0094] Step S7, spread the dried product in a crucible and put it into a tube furnace, set the heating rate to 5°C / min, introduce flowing nitrogen, heat to 850°C, keep the temperature for 4 hours for carbonization, and then cool naturally;
[0095] Step S8, putting the carbonized black product into a 20wt% ammonium bifluoride aqueous solution prepared in advance, stirring in a water bath at 50°C and 750rpm overnight, then vacuum filtering and cleaning with pure water, and finally drying by air at 65°C to obtain a hollow mesoporous carbon sphere F sample.
[0096] Figure 6 The characterization diagram of the SEM and TEM test is shown in Figure 1. It can be seen that the sample prepared by doubling the amount of each reactant compared with Example 5 is still spherical, but there are many solid and broken pieces. The shell thickness is also between 30-60nm, and the BET data shows that the specific surface area is 480m 2 / g, pore diameter of 7nm, pore volume of 0.92cm 3 / g, which may be due to the small and uneven reaction contact surface, resulting in that neither the carbon source distribution nor the hydrolysis of silicon dioxide reached the better state of the previous embodiment. However, it can still be seen that this method has the potential for scale-up production.
Claims
1. A method for preparing hollow mesoporous carbon spheres, characterized in that: The following steps are involved: Step S1, mixing ethanol, water and aqueous ammonia to prepare an aqueous ammonia ethanol solution; Step S2, adding tetraethyl orthosilicate to an ammonia ethanol solution to react, and then adding a mixed solution of water and ethanol to continue the reaction; Step S3, adding a template solution to the reaction solution of step S2 for reaction, wherein the template solution is a 20-35wt.% CTAC solution, and the amount of the template solution is 1 / 10 of the volume of the reaction solution of step S2; Step S4, adding resorcinol, formaldehyde solution and tetraethyl orthosilicate to the reaction solution of step S3 to carry out reaction; Step S5, transferring the reaction solution of step S4 to a hydrothermal reactor for reaction; Step S6, washing the reactant obtained in step S5 by centrifugation with ethanol and drying in vacuum; Step S7, carbonizing the dried product in step S6 under a nitrogen atmosphere; Step S8, adding the carbonized product in step S7 to an ammonium bifluoride solution for reaction, washing with water and then drying to obtain hollow mesoporous carbon spheres.
2. The method for preparing hollow mesoporous carbon spheres according to claim 1, characterized in that: In step S1, the volume ratio of ethanol, water and ammonia water in the ammonia ethanol solution is 100:20:
3.
3. The method for preparing hollow mesoporous carbon spheres according to claim 2, characterized in that: In step S2, the amount of ammonia ethanol solution is 60-80 ml, the volume ratio of tetraethyl orthosilicate to ammonia water in the ammonia ethanol solution is 5:3, the reaction conditions are 20-45°C, 300-500rpm, and the reaction time is 5-12h; the amount of the mixed solution of water and ethanol is 300-400 ml, the volume ratio of water and ethanol is 6:1, and the conditions for continuing the reaction are 20-45°C, 300-500rpm, and the reaction time is 15-40min.
4. The method for preparing hollow mesoporous carbon spheres according to claim 1, characterized in that: In step S3, the reaction conditions are 20-45° C., 300-500 rpm, and reaction time 15-40 min.
5. The method for preparing hollow mesoporous carbon spheres according to claim 3, characterized in that: In step S4, the amount of resorcinol used is 0.5-1.5 g, the amount of formaldehyde solution used is 0.75-2 ml, the amount of tetraethyl orthosilicate used is 3-5 ml, and the reaction conditions are 20-45° C., 300-500 rpm, and the reaction time is 14-20 h.
6. The method for preparing hollow mesoporous carbon spheres according to claim 1, characterized in that: In step S5, the reaction conditions are 100-150° C. for 20-30 hours.
7. The method for preparing hollow mesoporous carbon spheres according to claim 1, characterized in that: In step S6, the centrifugal washing with ethanol is performed by centrifugal washing with ethanol at a rotation speed of 9000-11000 rpm, and the vacuum drying condition is 50-70° C. for 12 hours.
8. The method for preparing hollow mesoporous carbon spheres according to claim 1, characterized in that: In step S7, the carbonization conditions are to increase the temperature to 700-900°C at a heating rate of 3-8°C / min and keep the temperature for 2-5h.
9. The method for preparing hollow mesoporous carbon spheres according to claim 1, characterized in that: In step S8, the concentration of the ammonium bifluoride solution is 10-30 wt.%, the reaction conditions are 20-60°C, 300-600 rpm, 12h, and the drying conditions are 50-75°C.